THE PRINCIPLE OF JUSTICE IN THE RULES OF FIQH SIYASAH AND ITS APPLICATION IN INDONESIA - okta, Oktaviano Afrizal (Politea : Jurnal Politik Islam, 2024)
This study examines the principle of justice in the principles of fiqh siyasah and its application in Indonesia as the country with the largest Muslim population in the world. Fiqh siyasah combines understanding sharia law (fiqh) with the art of leadership and governance (siyasah). Justice in fiqh siyasah is a fundamental principle that colours every government policy and action. The basis of the principle of justice is sourced from the Qur'an, such as QS An-Nisa verses 58, 135 and QS Al-Ma'arij verses 24-25, which order to uphold justice in law, testimony, and welfare distribution. The application of justice in Indonesia can be seen in law enforcement without discrimination, trustworthy governance, economic justice, protection of minority groups, and equal access to education. However, challenges, such as corruption, discrimination, and gaps, must be overcome to realize justice fully according to the guidance of fiqh siyasah. This study uses a qualitative and literature study approach to produce an in-depth understanding of the definition of justice in siyasah Aaliyah to contribute to developing fair public financial policies